2011
DOI: 10.5688/ajpe75472
|View full text |Cite
|
Sign up to set email alerts
|

An Elective Psychiatric Course to Reduce Pharmacy Students’ Social Distance Toward People With Severe Mental Illness

Abstract: Objective. To determine whether an elective course on mental health could reduce pharmacy students' social distance toward people with severe mental illness. Design. Course activities included assigned readings, class discussions, student presentations, review of video and other media for examples of social distance, presentations by patients with mental illness, and visits to hospitalized patients in a variety of psychiatric settings. Assessment. The Social Distance Scale (SDS) was administered at the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…Congruent with previous studies, 22,24,25,28,45,46 our study showed significant decreases in separation stigma postintervention. Higher scores (more stigmatizing attitudes) were associated with more personal social relationships such as marriage or sharing living space as opposed to lower scores (less stigmatizing) for less personal social relationships such as being a coworker or living next door.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Congruent with previous studies, 22,24,25,28,45,46 our study showed significant decreases in separation stigma postintervention. Higher scores (more stigmatizing attitudes) were associated with more personal social relationships such as marriage or sharing living space as opposed to lower scores (less stigmatizing) for less personal social relationships such as being a coworker or living next door.…”
Section: Discussionsupporting
confidence: 82%
“…While several studies measure changes in stigma, attitudes toward mental illness, and attitudes toward providing pharmacy services, 22,24,25,28 few examine mental health knowledge (MHK) among pharmacy students. Among published studies, MHK was operationalized in various ways including focusing on identifying medications or specific mental illnesses and recognizing recommended interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this is grounded in institutional stigmatization toward mental health patients requires further investigation, but such attitudes help to explain study findings that pharmacy students hold/have stigmatizing views toward these patients. [11][12][13] Pharmacy educators in the United Kingdom therefore need to consider how curricula can be modified to improve contextualization and increase patient contact. Without major reforms to academic delivery (which are currently being considered at the government level 16 ), the provision of meaningful work-based placements of pharmacy students seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…A 2007 study of US colleges and schools revealed that a wide range of mental health conditions were taught in the pharmacy curriculum, although the time devoted to the different conditions varied considerably. 7 Given that UK mental health services have dramatically changed since the work of Branford, moving from predominantly hospitalbased care to tailored local community care, [9][10] and that studies have shown that pharmacy students have stigmatizing views regarding mental health illnesses [11][12][13] the authors felt that reassessment of mental health teaching in UK schools of pharmacy was needed.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with those of previous studies showing a decrease in pharmacy students' preferred social distance after contact in an educational setting with consumer educators who have a mental illness. 17,22,26,33 We have previously shown that although most pharmacists have extensive professional experience with people who have depression as a result of seeing them in the pharmacy workplace at least weekly or even daily, most pharmacists endorse social distance. 11 The current results provide further evidence that it is not the quantity but the quality and the type of contract with people with mental illness that influence stigma reduction.…”
Section: Discussionmentioning
confidence: 99%